Parallel Processing with Promises. - RATHBUN, SPENCER (Communications of the ACM, 2015)
The article discusses the management and coding of distributed computer systems and asynchronous programming. The author reflects on the use of an abstraction known as promises to simplify asynchronous function call management and parallel processing. Other topics include the writing of concurrent processing systems, the algorithmic design of promises, the central authority of the Node.js process, health checks for processing workers, and synchronization among central authorities in multiple servers or processes.